2023
DOI: 10.3389/fimmu.2023.1134663
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal immune microenvironment of endometriosis: Role and therapeutic perspectives

Abstract: Endometriosis, an estrogen-dependent chronic inflammatory disease characterized by the growth of endometrium-like tissues outside the uterine cavity, affects 10% of reproductive-age women. Although the pathogenesis of endometriosis is uncertain, it is widely accepted that retrograde menstruation results in ectopic endometrial tissue implantation. Given that not all women with retrograde menstruation develop endometriosis, immune factors have been hypothesized to affect the pathogenesis of endometriosis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 185 publications
(228 reference statements)
0
11
0
Order By: Relevance
“…Oestrogens are crucial for the growth of endometrial cells, and environmental factors like pesticides and toxicants may contribute to abnormal cell development in women with endometriosis by impacting the production and breakdown of oestradiol [ 166 ]. An oestrogenic microenvironment is established close to endometriotic lesions due to the local accumulation of oestradiol [ 167 ]. A network of genes including greb1, myc, and ccnd1 that govern cell mitogenesis is activated when there are high local concentrations of oestradiol and overexpression of estrogen receptor alpha (ERα) and ERβ [ 168 ].…”
Section: The Role Of Vitamin D In the Pathogenesis Of Endometriosismentioning
confidence: 99%
“…Oestrogens are crucial for the growth of endometrial cells, and environmental factors like pesticides and toxicants may contribute to abnormal cell development in women with endometriosis by impacting the production and breakdown of oestradiol [ 166 ]. An oestrogenic microenvironment is established close to endometriotic lesions due to the local accumulation of oestradiol [ 167 ]. A network of genes including greb1, myc, and ccnd1 that govern cell mitogenesis is activated when there are high local concentrations of oestradiol and overexpression of estrogen receptor alpha (ERα) and ERβ [ 168 ].…”
Section: The Role Of Vitamin D In the Pathogenesis Of Endometriosismentioning
confidence: 99%
“…In addition to the intricate interplay involving macrophages and the aforementioned mechanisms, it is essential to address the role of fibrosis in this context. In this sense, TGF-β secreted by M2 macrophages induces fibrosis, as it promotes the differentiation of fibroblasts into myofibroblasts and stimulate the synthesis of collagen and fibronectin[ 81 - 83 ]. On the other hand, Barcz et al [ 84 ] suggests that increased levels of VEGF are negatively associated to endometriosis-related pelvic fibrotic adhesions.…”
Section: Immune Dysregulation In Endometriosis and Estrogen Dependenc...mentioning
confidence: 99%
“…Macrophages also play a role in neurogenesis and, consequently, in the onset of endometriosis-associated pain[ 85 ]. Overall, nerve fibers originating from endometriotic lesions have the capacity to secrete chemokines such as CCL2 and CSF-1, which, as previously discussed, are pivotal in the recruitment of macrophages[ 81 , 86 ]. As a result, macrophages release neurotrophic factors, including brain-derived neurotrophic factor and neurotrophin-3, thus contributing to the heightened sensitivity and pain experienced by individuals with endometriosis[ 86 ].…”
Section: Immune Dysregulation In Endometriosis and Estrogen Dependenc...mentioning
confidence: 99%
“…One of the hallmarks of endometriosis is the dysregulation of the immune system, which contributes to the establishment, maintenance, and growth of ectopic endometrial lesions. Several studies have shown that endometriosis is associated with altered immune cell populations, cytokine pro les, and in ammatory responses in the peritoneal cavity and systemic circulation (4). Moreover, endometriosis lesions exhibit features of immune evasion and resistance to apoptosis, similar to cancer cells.…”
Section: Introductionmentioning
confidence: 99%